Pelatihan Manajemen Toko Bagi Pengurus/Pengelola Primer Koperasi Kartika D-01 dan di Lingkungan Korem 074 Warastratama Surakarta - Supriyadi, Deddy (LPPM Universitas Koperasi Indonesia, 2024)
Shop Management Training for Cooperative Primary Managers/Managers in the ranks of Korem 074 Warastratama Surakarta was carried out to improve the competency of primary cooperative human resources in the ranks of Korem Warastratama Surakarta. This was done based on a request from the management of the Kartika D-01 Cooperative, which is one of the primary cooperatives in the ranks of Korem Warastratama, because it was felt that there was a need to improve more Store Management. Considering the importance of this material and to optimize the benefits of this training, the training was finally attended by all representatives of primary cooperative administrators/managers in the ranks of Korem 074 Warastratama (a total of 17 cooperatives). The material presented includes: Consumer Cooperatives, Retail Mix Strategy, Standard Operation Procedure Retail Stores (Retail Store SOP) and Excellent Service. The training method used is the andragogy method, this method was chosen because it was considered appropriate to the profile of the training participants. Participants took part in the training enthusiastically, several participants submitted questions and responses based on their experience managing a shop. In general, participants felt enlightened, realized and understood the need to implement good store management to be able to reach consumers and compete. Even though consumers are members who are owners of cooperatives, in reality, because members live in urban areas, they have the choice to meet their daily needs in cooperatives or non-cooperatives. Thus, cooperatives are in a competitive market situation and conditions. For this reason, cooperatives must be able to compete